Strategic Decision Comprehensiveness and New Product Development Outcomes in New Technology Ventures - Atuahene‐Gima, Kwaku; Li, Haiyang (Academy of Management Journal, 2004)
With a sample of new technology ventures in China, we investigated the contingent effect of strategic decision comprehensiveness on new product performance and product quality. The relationship between strategic decision comprehensiveness and new product performance was negatively moderated by technology uncertainty but positively moderated by demand uncertainty. The effect of decision comprehensiveness on new product quality was positively moderated by demand uncertainty but unaffected by technology uncertainty. The comprehensiveness-performance link emerges as more complex than previous research has shown.